ANALISIS KUALITAS APARAT PENGAWAS INTERN PEMERINTAH DALAM PENGAWASAN KEUANGAN DAERAH (Studi pada Pemerintah Daerah Kabupaten Minahasa Tenggara) - Lumbantobing, Josua H.R.; Saerang, David Paul Elia; Wokas, Heince (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2015)
This study aimed to analyze the quality of internal government regulatory authorities. A common problem in this study is the finding of the audit that is not detected by the inspectorate apparatus as an internal auditor, but was found by the external auditor, the Supreme Audit Agency (BPK). The method used in this research is descriptive qualitative. As in qualitative research, the authors use the method of in-depth interviews and Forum Group of Discussion with informants who have knowledge related to this research. The results show, that became key points of analysis of internal audit quality authorities Southeast Minahasa regency government is to meet the needs of the Inspectorate competent authorities by providing technical guidance, education and ongoing training to improve quality. Not doing too frequent mutations, mutation should be done in accordance with the competence of the employees. While that is key to improving the quality of the Inspectorate is a strong commitment of the Head of Region for the creation of good and clean government to push for a more active role Inspectorate. The existence of the fulfillment of the budget for the Inspectorate of 1%. This study certainly has limitations that can not be ignored. Therefore, further research is needed as a future research agenda.